2004
DOI: 10.1021/ie0498807
|View full text |Cite
|
Sign up to set email alerts
|

Nanoporous Low-Dielectric Constant Polyimide Films via Poly(amic acid)s with RAFT-Graft Copolymerized Methyl Methacrylate Side Chains

Abstract: Poly[N,N′-(1,4-phenylene)-3,3′4,4′-benzophenonetetracarboxylic amic acid] (PAmA) with grafted poly(methyl methacrylate) (PMMA) side chains (PAmA-g-PMMA) was synthesized via thermally induced graft copolymerization of methyl methacrylate (MMA) with ozone-pretreated PAmA in the reversible addition-fragmentation chain-transfer (RAFT)-mediated process. The graft copolymers were characterized by nuclear magnetic resonance (NMR), elemental analysis, X-ray photoelectron spectroscopy (XPS), thermogravimetric analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 25 publications
(48 reference statements)
1
38
0
Order By: Relevance
“…[228] Most work has used ATRP or NMP, though papers on the use of RAFT polymerization have begun to appear. [229][230][231][232][233][234][235] The first to apply RAFT in this context were Tsujii et al [229] and Brittain and coworkers. [230,231] Recent papers describe RAFT polymerization from plasma-treated Teflon surfaces [232] and ozonolyzed polyimide films.…”
Section: Microgelsmentioning
confidence: 99%
See 1 more Smart Citation
“…[228] Most work has used ATRP or NMP, though papers on the use of RAFT polymerization have begun to appear. [229][230][231][232][233][234][235] The first to apply RAFT in this context were Tsujii et al [229] and Brittain and coworkers. [230,231] Recent papers describe RAFT polymerization from plasma-treated Teflon surfaces [232] and ozonolyzed polyimide films.…”
Section: Microgelsmentioning
confidence: 99%
“…[230,231] Recent papers describe RAFT polymerization from plasma-treated Teflon surfaces [232] and ozonolyzed polyimide films. [235] The approach used in these and most other studies [230][231][232][233][234][235] has been to immobilize initiator functionality on the surface by chemical or plasma modification and use this to initiate polymerization in the presence of a dithioester RAFT agent. Tsujii et al [229] have indicated that some difficulties arise in using RAFT for grafting from particles because of an abnormally high rate of radical-radical termination caused by a locally high concentration of RAFT functionality.…”
Section: Microgelsmentioning
confidence: 99%
“…Polyimides (PI) are a favored material because of their high thermal stability, low stress coefficient of thermal expansion, low dielectric constant, high resistivity, and high dielectric breakdown [120,[130][131][132][133][134][135]. For instance, Lee et al [130] managed to develop a nanoporous PI films (thickness: 200 lm) with pore sizes from 10 to 40 nm, a porosity around 20%, and a dielectric constant of 2.25 (a reduction of 31% with respect to the solid).…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…By this methodology, various ultra low-k PIs have been reported [10][11][12][13][14]. However, the attempts further reducing the k values of PIs below 1.5 seem to be more challenging because the conventional methods could only achieve a very limited air loading (<60%, volume ratio).…”
mentioning
confidence: 99%